Religious Harmony Construct Amid A Plural Community in East Java - Dina Mardiana; Muhammad Yusuf; Asyraf Isyraqi Jamil (KARSA Journal of Social and Islamic Culture, 2020)
This study examined the harmonization of five religions (Islam, Catholicism, Protestantism, Hinduism, and Buddhism) that are adhered to by the people of Mojorejo Village, Batu, East Java. This village has an important role, as it becomes the first area in Batu, East Java – that implement and develop the concept of religious pluralism and harmonization in one village area thus it has been awarded as “A Village that is Aware of Religious Harmony” from the government of Batu. Therefore, this study aimed to understand the constructs of religious harmony that have been successfully established in Mojorejo Village, Batu, East Java. The theory underlying this study is Nurcholis Madjid’s theory of humanist pluralism. This study used a qualitative approach to produce descriptive data in the form of oral, written, and observable behavior. Through three data collection methods (observation, in-depth interview, a study of documents), this study concludes that the religious harmony construct of the Mojorejo Village community is established from a pattern of accustoming mutual respect among villagers which is carried out both naturally and sustainably. This continuity manifests through cooperation in three ways: religious, social, and cultural cooperation so that it can lead to the emerge of perspectives, ideas, and a social environment capable of maintaining and preserving religious plurality in harmony. Therefore, the application of religious harmony in Mojorejo Village, Batu, East Java can be used as an alternative solution for other areas in locating and facilitating religious plurality so that it remains harmonious amid a pluralistic community.